Use of Copyrighted Works for Education and Research in EU Law - Veikša, Ingrīda (Journal of Education Culture and Society, 2026)
Aim. This research aims to analyse the legal framework governing the use of copyrighted works for educational and research purposes within the European Union (EU). It focuses on the balance between authors’ rights and public interest, emphasising exceptions codified in the InfoSoc Directive (2001/29/EC) and the CDSM Directive (2019/790), with comparative insights from selected EU Member States.Methods. The research employs a comparative legal analysis of EU directives and national legislation across Latvia, Lithuania, Estonia, Hungary, France, Germany, Spain, Poland, Slovenia, Finland, and Switzerland.Results. Findings reveal significant divergence in national implementation. Latvia, Lithuania, Estonia, Hungary, France, and Switzerland offer full exceptions without remuneration. Finland uses extended collective licensing, while countries like Slovenia, Poland, Spain, and Germany adopt hybrid models requiring partial compensation. The CDSM Directive enhances digital and cross-border educational use, but national discretion leads to uneven application.Conclusions. EU copyright law provides a structured yet flexible framework for educational use, but harmonisation remains incomplete. Clearer guidelines and broader awareness are needed to ensure lawful use of copyrighted materials in academia while safeguarding creators’ rights. Early intellectual property education and simplified licensing systems could further support compliance and innovation.Originality. This research contributes original insights by evaluating the implementation practice of EU directives in the laws of different countries, revealing the interplay between harmonised legal norms and national educational practices. It advances cognitive understanding by identifying four core criteria - educational institution, non-commercial purpose, secure electronic environment, and illustrative purpose as the pillars of lawful educational use.